Production of ‘Aliança’ papaya seedlings under different dosages and sources of Lithothamnion sp - Pereira Ramos, Elmo; Borges de Aguiar, Diego; Mota Barbosa, Ana Kelly; de Souza Oliveira, Vinicius; de Oliveira Arantes, Lúcio; Romais Schmildt, Edilson; Ralph Falqueto, Antelmo; Alves Fernandes, Adriano; Dousseau-Arantes, Sara (Frontiers in Plant Science, 2025)
IntroductionThe production ofpapaya seedlings is one of the main steps for establishing crops that present maximum quality performance. Nutritional availability is one of the factors limiting the formation process of quality seedlings, and fertilization is often done without technical criteria. Thus, the objective of this study was to evaluate the effect of different doses of Lithothamnion sp., obtained from different sources, on the development and growth of ’Aliança‘ papaya seedlings.MethodsThe study was developed at the Experimental Farm of the Capixaba Institute of Research, Technical Assistance, and Rural Extension, in the municipality of Linhares, north of the state of Espírito Santo. The experimental design used was randomized blocks in a factorial scheme, where the first factor was composed of three commercial sources of Lithothamnion sp. (LT Supra®; Algen® and Primaz®). The second factor was composed of six different doses, namely: 0; 2; 4; 6; 8; and 10 kg m-3 of Lithothamnion sp. At 37 days after sowing, the seedlings were evaluated for the following characteristics: germination percentage; leaf area; stem length; stem mass fraction; root length; stem diameter; leaf dry mass; stem dry mass; root dry mass; and total dry mass. The content of nitrogen, phosphorus, potassium, calcium, magnesium, and sulfur in the leaves and roots was also evaluated.ResultsThe use of Lithothamnion sp. on ’Aliança‘ papaya seedlings promoted leaf and stem growth and development, dry matter accumulation, and improved germination percentage. Lithothamnion sp. from the coast of Espírito Santo (LT supra®) promoted significant gains in germination percentage, leaf area, stem length, root collar diameter, leaf dry matter, stem dry matter, and total dry matter. Lithothamnion sp. from the coast of Maranhão (Algen®) and Bahia (Prima®) increased leaf phosphorus and root sulfur levels.DiscussionLithothamnion sp. promoted a biostimulant effect with improved growth and development in ’Aliança‘ papaya seedlings, with a dosage close to 4 kg m-3, with the LT supra® product being the most recommended.